Validated space radiation exposure predictions from earth to mars during Artemis-I - Tony C. Slaba; Shirin Rahmanian; Stuart George; Diego Laramore; John W. Norbury; Charles M. Werneth; Cary Zeitlin (npj Microgravity)
Abstract Accurate characterization of space radiation exposure is critical to assess and communicate multiple health risks for crewmembers participating in future exploration missions. A combination of models and on-board instruments are utilized to meet this requirement. In this work, computational models are evaluated against spaceflight measurements taken within the International Space Station, the Orion spacecraft, the BioSentinel CubeSat, and on the Martian surface. All calculations and measurements cover the exact same time period defined by the Artemis-I mission, and all model calculations were performed blind—without prior knowledge of the measurements. The models are shown to accurately characterize the absorbed dose-rate in highly complex and diverse shielding configurations in locations from Earth to Mars.